Path Analysis on Factors Affecting the Willingness to Accept Vasectomy among Men in Sanden Community Health Center, Bantul, Yogyakarta, Indonesia - Dechoni Rahmawati; Bhisma Murti; Argyo Demartoto (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: Family Planning Program 0r Program Keluarga Berencana (KB) is a program initiated by the government to improve the quality of life in Indonesia. One of contraception methods for men is MOP (Operation Method Man) or a vasectomy. Most of society norms regard that family planning is the area of women and men do not need to be involved is also one reason for the lack of participation of men in family planning. This study aimed to investigate of path analysis affecting the willingness of husband as vasectomy acceptors.Subjects and Method: This was observational analytic study with case control design. This was conducted in Puskesmas Sanden Bantul, Indonesia. A total sample of 90 respondents was selected by Fixed Disease Sampling. Data analysis used Path Analysis.Results: There is no direct correlation between attitude and willingness of husband as an acceptor of vasectomy (b= 3.21; 95% CI= 1.74 to 4.69; p <0.001), an indirect correlation between subjective norms and husband’s willingness as vasectomy acceptors (b= 2.08; 95% CI= 0.44 to 3.72; p= 0.013), perceived behavioral (b= 1.73; 95% CI= 0.25 to 3.20; p= 0.021), a direct correlation between the perception of behavioral control and a husband’s willingness as an acceptor of vasectomy (b= 1.49; 95 % CI= 0.36 to 3.62; p= 0.010) intention and willingness husband's vasectomy using (the value of coefficient b= 2.13; 95 % CI=1.00 to 3.27; p <0.001).Conclusion: There is an indirect and direct correlation of husband’s willingness as an acceptor of vasectomy by Theory of Planned Behaviour.Keywords: attitude, subjective norms, perceived behavioral, intention, willingnessCorrespondence: Dechoni Rahmawati. School of Health Jenderal Ahmad Yani, Yogyakarta.Journal of Health Promotion and Behavior (2016), 1(1): 26-31https://doi.org/10.26911/thejhpb.2016.01.01.04